Identiﬁcation of Terrestrial Wildlife by the Use of Camera Traps at Gunung Ayam, Gunung Stong State Park - Muhammad Syazwan Abdul Latif (2018)
A recent terrestrial wildlife survey was conducted at Gunung Ayam, Gunung Stong State Park, Kelantan. The main objectives of this study were to provide a preliminary checklist of terrestrial wildlife at Gunung Ayam by the use of camera trapping method and analyse the species richness of species captured from the checklist. 3 camera traps were used baited with salt (sodium chloride, NaCl). These traps were placed for 40 days in 3 different locations. ln total, 10 individuals of mammal were recorded comprising from 7 species. The potential factors that inﬂuencing the capturing rate; are fruit season, weather and availability of water source. More study is needed for this study research to obtain more data.